Relevansi Kurikulum dalam Kebijakan Pendidikan - J Drost, SJ (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2001)
In education system of modern society, schoolings -- the formal education system from primary schools to universities -- have always been the main institution for teaching and learning process. It has to be understood that the success of formal education is determined by capacity and motivation. In this regards, curriculum is a critical factor to support individual capacity and mot ivat ion. In Indonesian education system, curriculum for primary school (SD) is quite good and has an appropriate standard in comparison with international best practices. However, there are substantial problems in the curriculum for secondary and high schools. Aside from the fact that the national test (Ebtanas) system for primary school is not suitable for primary school children, there are some substantial flaws in the National Curriculum of 1994. This curriculum could be an excellent manual for the best high school children. However, as it is used across the board (for all cohort of schoolchildren achievements), the quality standard of education at this level has been brought down. At the same time, there is limited alternative at secondary level (SLTP) as well as higher level (SMU) to build skills for weaker students, some basic education needs that can presumably be fulfilled by vocational schools. Universities have to focus on degree programmes instead of opening more diploma (D3) programmes. Curriculum in highschools and universities have to be linked with character building and capacity building. Education has to be able to develop a competent, professional, and responsible human resources. These are the ultimate goal of teaching and learning process.